A binder for polished aluminum for tooling and preparation method thereof

By optimizing the formulation of polyurethane adhesives, using polyol compositions and nano-silica raw materials, the problems of attenuation of bonding strength and high glue application amount during bonding of aluminum honeycomb boards are solved, and efficient and low-cost bonding effect is achieved.

CN119432302BActive Publication Date: 2025-05-02SHANGHAI JINQIANG ADHESIVE

Patent Information

Application Number
CN202510019921.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-05-02
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

When used in the assembly of aluminum honeycomb boards, the existing polyurethane adhesives have problems with attenuation of bond strength after curing, and while ensuring the bond strength, the glue application amount is high, which increases the actual application cost.

Method used

By controlling the selection and ratio of polyols, dispersants, and catalysts, a binder of a polyol composition including castor oil, polyether polyol and propylene glycol is prepared, combined with raw materials such as nanosilicon dioxide and activated calcium, the formulation of the binder is optimized, and efficient bonding to glossy aluminum and honeycomb plates is achieved.

Benefits of technology

It achieves a high roller peel strength (≥80N*mm/mm) at a lower glue application, which reduces production costs, improves construction convenience, and does not require additional grinding steps, greatly improving the production efficiency of honeycomb aluminum plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432302B_ABST
    Figure CN119432302B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane adhesives, in particular to an adhesive for tooling polished aluminum and a preparation method thereof. The adhesive comprises a component A and a component B, wherein the raw materials for preparing the component A comprise at least 25-40 parts of a polyol composition, 50-75 parts of a calcium filler, 0.1-0.3 parts of a dispersant, 0.1-0.3 parts of a catalyst, 1-4 parts of a molecular sieve, 0.01-0.2 parts of a defoamer and 0.1-0.5 parts of nano silicon dioxide, and the component B comprises at least isocyanate. By controlling the selection and coordination of the polyol, the dispersant and the catalyst in the system and the addition amount of each raw material, when the provided adhesive is used for bonding the polished aluminum (1-2 mm) to a honeycomb panel, the roller peel strength is ≥60 N*mm / mm, thereby meeting the actual external wall application requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane adhesives, in particular to an adhesive for tooling polished aluminum and a preparation method thereof. Background Art

[0002] As a common building material, aluminum honeycomb panels are widely used in exterior walls and ceilings in the construction field due to their many advantages such as light weight, high strength and high rigidity. They are also suitable for vehicle and ship decoration, aviation, aerospace and other fields. At present, aluminum honeycomb panels are mainly installed by bonding with polyurethane adhesives. Most polyurethane adhesives will not immediately reach a high bonding strength during bonding. It is also necessary to cure the polyurethane adhesive to produce a sufficiently high bonding force with the substrate. During the gradual curing process, the polyurethane adhesive will show a state of gradually increasing body strength. When the body strength is lower than the interface bonding strength, cohesive failure occurs. At this time, the bonding strength obtained is the body strength of the adhesive, which is an ideal mode. However, when the existing polyurethane adhesives are used for aluminum honeycomb panel assembly, there is a problem that the bonding strength of the polyurethane adhesive after curing shows a decay phenomenon. The Chinese patent (authorization announcement number CN111454686B) discloses a polyurethane adhesive and its preparation method, and an aluminum honeycomb panel. The polyurethane prepolymer with hydroxyl end is synthesized by prepolymerization, and compounded with bisphenol A / propylene oxide polyether diol to ensure the bonding strength and flexibility of the polyurethane adhesive. However, the amount of glue applied is relatively high. For aluminum plates with a thickness of less than 1 mm, the amount of glue applied is 400±10g / m 2 The corresponding roller peel strength cannot be guaranteed under the conditions of , which greatly increases the actual application cost. The Chinese patent (publication number CN115975583A) discloses a formaldehyde-free plant adhesive, which mainly uses a specific polyol polymer and ethylenediamine as a small molecule chain extender to improve the glass transition temperature of the polyurethane adhesive, prolong the curing time, and avoid the problem of too high hardness caused by too fast curing rate and hardness reduction after long-term use. However, it cannot guarantee the roller peel strength of ≥60N*mm / mm for bonding smooth aluminum and honeycomb panels, and cannot meet the actual exterior wall application requirements. Summary of the invention

[0003] In order to solve the above problems, the present invention provides an adhesive for tooling polished aluminum. By controlling the selection and combination of polyols, dispersants, and catalysts in the system and controlling the addition amount of each raw material, when the provided adhesive is used for bonding polished aluminum (1-2mm) to honeycomb panels, the roller peel strength is ≥60N*mm / mm, which meets the actual exterior wall application requirements.

[0004] On one hand, the present invention provides a binder for polished aluminum of tooling, comprising component A and component B. Calculated by weight, the raw materials for preparing component A at least comprise 25-40 parts of a polyol composition, 50-75 parts of a calcium filler, 0.1-0.3 parts of a dispersant, 0.1-0.3 parts of a catalyst, 1-4 parts of a molecular sieve, 0.01-0.2 parts of a defoamer, and 0.1-0.5 parts of nano-silicon dioxide; and component B at least comprises isocyanate.

[0005] As a preferred technical solution, the polyol composition comprises at least castor oil, polyether polyol and propylene glycol; the mass ratio of castor oil, polyether polyol and propylene glycol is (20-30): (4-10): (0.1-1), preferably (20-30): (5-9.7): (0.3-0.4).

[0006] As an example, the mass ratio of castor oil, polyether polyol and propylene glycol is 20:4:0.1, 20:4:0.4, 20:4:0.8, 20:4:1, 20:5:0.3, 26.4:4:0.1, 26.4:4:0.4, 26.4:4:1, 26.4:5.8:0.1, 26.4:5.8:0.4, 26.4:5.8:1, 30:7:1, and 30:9.7:0.3.

[0007] As a preferred technical solution, the polyether polyol includes polyether polyol 1 and polyether polyol 2. Preferably, the mass ratio of polyether polyol 1 to polyether polyol 2 is (2-5):(3-6), preferably (2-4.5):(3-5.2).

[0008] As an example, the mass ratio of the polyether polyol 1 to the polyether polyol 2 may be 2:3, 2:4, 2.5:3, 2.5:3.3, 2.5:3.5, 2.5:3.8, 2.8:3, 3:3, 3:4, 4:3, 4:5, or 4.5:5.2.

[0009] As a preferred technical solution, the polyether polyol 1 has a hydroxyl value of 300-400 mgKOH / g and a viscosity of 200-400 mPa·s at 25°C.

[0010] As a preferred technical solution, the polyether polyol 2 has a hydroxyl value of 200-300 mgKOH / g and a viscosity of 20-200 mPa·s at 25°C.

[0011] Preferably, the polyether polyol 1 has a hydroxyl value of 335±10 mgKOH / g and a viscosity of 260-380 mPa·s at 25° C. (DMN500, sourced from Zibo Dexin Federal Chemical Industry Co., Ltd.).

[0012] Preferably, the polyether polyol 2 has a hydroxyl value of 280±10 mgKOH / g and a viscosity of 40-140 mPa·s at 25° C. (WANOL C2004, Wanhua Chemical).

[0013] As a preferred technical solution, the calcium filler at least includes active calcium, calcium oxide and calcium carbonate.

[0014] Preferably, the mass ratio of the active calcium, calcium oxide and calcium carbonate is (5-15):(1-3):(40-70), preferably (5-9.9):1.6:(42.4-63.5).

[0015] As an example, the mass ratios of the active calcium, calcium oxide and calcium carbonate are 5:1:45, 5:1:60, 5:3:45, 5:3:60, 15:1:45, 15:1:60, 15:3:45, 15:3:60, 9.9:1.6:52.1, 9.9:1.6:63.5, and 5:1.6:42.4.

[0016] As a preferred technical solution, the particle size of the active calcium, calcium oxide and calcium carbonate is 800 mesh-1250 mesh.

[0017] As a preferred technical solution, the BET specific surface area of ​​the nano-silicon dioxide is 150-250m² / g, preferably AEROSIL 200.

[0018] As a preferred technical solution, the catalyst at least includes a tertiary amine catalyst, preferably Evonik SA102.

[0019] As a preferred technical solution, the dispersant is a dibasic acid ester (DBE).

[0020] As a preferred technical solution, the molecular sieve is 4A molecular sieve.

[0021] As a preferred technical solution, the defoaming agent at least includes SX08 defoaming agent (Sixin Technology).

[0022] The adhesive provided by the present invention is mainly optimized for the problems existing in the actual production and application of aluminum honeycomb panels. At present, during the preparation process of aluminum honeycomb panels, the aluminum plates usually need to be polished or pre-coated before being coated with glue and composited, and higher composite strength needs to be provided at a higher glue coating amount, which greatly increases the process flow and application cost in the actual application process, and is not easy to achieve large-scale promotion and application. The present invention has found through a large number of experimental investigations that by adopting a polyol composition including castor oil, polyether polyol and propylene glycol, especially when the polyether polyol includes a polyether polyol 1 having a hydroxyl value of 300-400 mgKOH / g and a viscosity of 200-400 mPa·s at 25°C and a polyether polyol 2 having a hydroxyl value of 200-300 mgKOH / g and a viscosity of 20-200 mPa·s at 25°C, under the coordinated effect of other raw materials in the system, the provided adhesive can be directly used for the composite between the smooth aluminum plate and the honeycomb plate, without the need to add an additional polishing step of the smooth aluminum plate, thereby greatly improving the production efficiency of the honeycomb aluminum plate, and the roller peel strength is ≥80N*mm / mm, which meets the actual use requirements.

[0023] Furthermore, by controlling the amount of dibasic acid ester (DBE) added in the system and coordinating the amount of active calcium, calcium oxide and calcium carbonate added in the system, the viscosity of the product is ensured to meet the requirements of the coating application while ensuring the bonding composite strength between the smooth aluminum plate and the honeycomb plate. Too high a viscosity will cause glue breakage and gun blockage, while too low a viscosity will cause sagging and an uneven glue layer.

[0024] Furthermore, based on the polyol composition and polymeric MDI used in the system, Evonik SA102 is preferably used as a catalyst to ensure the strength of the polyol composition after curing with the polymeric MDI, and to effectively avoid the problem of excessive hardness caused by too fast a curing rate and a decrease in hardness after long-term use.

[0025] As a preferred technical solution, the isocyanate is polymeric MDI, preferably Wanhua PM200.

[0026] As a preferred technical solution, the mass ratio of component A to component B is 100:(20-30), preferably 100:25.

[0027] On the other hand, the present invention provides a method for preparing a binder for polished aluminum of tooling, which comprises at least the following steps: mixing a polyol composition and nano-silicon dioxide by weight, adding a calcium filler and a molecular sieve for high-speed dispersion, adding a dispersant, a catalyst and a defoaming agent for stirring and dispersing, and then cooling to below 50° C. to obtain component A; when in use, component A and component B are stirred and mixed to obtain the binder.

[0028] The adhesive provided by the present invention achieves strong bonding at a lower amount of adhesive by optimizing the product formula system, greatly improves the construction convenience and reduces the production cost of the aluminum honeycomb panel, and is easy to realize large-scale industrial production.

[0029] Beneficial Effects

[0030] 1. The present invention provides an adhesive for tooling polished aluminum. By controlling the selection and combination of polyols, dispersants, and catalysts in the system and controlling the addition amount of each raw material, when the provided adhesive is used for bonding polished aluminum (1-2 mm) to honeycomb panels, the roller peel strength is ≥60N*mm / mm, meeting the actual exterior wall application requirements.

[0031] 2. The present invention adopts a polyol composition including castor oil, polyether polyol and propylene glycol, especially when the polyether polyol includes polyether polyol 1 with a hydroxyl value of 300-400 mgKOH / g and a viscosity of 200-400 mPa·s at 25°C and polyether polyol 2 with a hydroxyl value of 200-300 mgKOH / g and a viscosity of 20-200 mPa·s at 25°C, under the coordination of other raw materials in the system, the provided adhesive can be directly used for the composite between the smooth aluminum plate and the honeycomb plate, without the need to add an additional polishing step of the smooth aluminum plate, thereby greatly improving the production efficiency of the honeycomb aluminum plate, and the roller peel strength is ≥80N*mm / mm, meeting the actual use requirements.

[0032] 3. The present invention ensures that the viscosity of the product meets the requirements of curtain coating application while ensuring the bonding composite strength between the smooth aluminum plate and the honeycomb plate by controlling the addition amount of divalent ester (DBE) in the system and coordinating the addition amount of active calcium, calcium oxide and calcium carbonate in the system. If the viscosity is too high, the glue will break and the gun will be blocked, while if the viscosity is too low, it will sag and the glue layer will be uneven.

[0033] 4. Based on the polyol composition and polymeric MDI used in the system, Evonik SA102 is preferably used as a catalyst to ensure the strength of the polyol composition and polymeric MDI after curing, and to effectively avoid the problem of excessive hardness caused by too fast curing rate and decreased hardness after long-term use.

[0034] 5. The adhesive provided by the present invention achieves strong bonding at a lower amount of adhesive by optimizing the product formula system, which greatly improves the construction convenience while reducing the production cost of the aluminum honeycomb panel, making it easy to realize large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1-10 They correspond to the material breaking effects of Example 1 and Comparative Examples 1-9 respectively. DETAILED DESCRIPTION

[0036] Examples 1-3, Comparative Examples 1-9

[0037] Embodiments 1-3 and comparative examples 1-9 of the present invention provide a binder for polished aluminum for tooling, comprising component A and component B. The raw materials for preparing component A are shown in Table 1, and component B is polymerized MDI (Wanhua PM200). The mass ratio of component A to component B is 100:25.

[0038] Table 1

[0039]

[0040] On the other hand, Examples 1-3 and Comparative Examples 1-9 of the present invention provide a method for preparing a binder for polished aluminum tooling, comprising the following steps: stirring and mixing a polyol composition and nano-silicon dioxide by weight, adding a calcium filler and a molecular sieve for high-speed dispersion at a speed of 1500 r / min (high-speed dispersion will generate heat, and the colloid temperature can reach 70-80°C), adding a dispersant, a catalyst, and a defoaming agent, stirring and dispersing, and then cooling to below 50°C to obtain component A; when in use, stir and mix component A and component B to obtain the obtained component.

[0041] Performance Testing

[0042] 1. Viscosity: After component A and component B in the examples and comparative examples were uniformly mixed (time for 20 seconds), a viscometer was used for testing (viscometer model: Brookfield DV2TRVTJ05 rotor, 10 revolutions per minute, 25°C). The test results are shown in Table 2.

[0043] 2. Roller peel strength: According to the national standard GB / T1457-2005, component A and component B in the embodiment and comparative example were mixed evenly (time is 20s) and then sprayed onto the surface of smooth aluminum (1-2mm) (the amount of glue applied is 400g / m 2 ), compounded with honeycomb board, hot pressed at 70℃ for 10min, and the average roller peel strength after curing for 1 day, 3 days and 7 days was calculated. The results are shown in Table 2.

[0044] 3. Material breaking effect: Mix component A and component B in the embodiment and comparative example evenly (time is 20s) and then spray coat them on the surface of smooth aluminum (1-2mm) (the amount of glue applied is 400g / m 2 ), compounded with honeycomb board, hot pressed at 70℃ for 10min, cured for 24h, the honeycomb board and the smooth aluminum are peeled off (the peeling force of each embodiment and the comparative example is the same), the material breaking effect is shown in Figure 1-10 .

[0045] Table 2

[0046]

Claims

1. A binder for polished aluminum for tooling, characterized in that: The invention comprises component A and component B. The raw materials for preparing component A comprise at least 25-40 parts of a polyol composition, 50-75 parts of a calcium filler, 0.1-0.3 parts of a dispersant, 0.1-0.3 parts of a catalyst, 1-4 parts of a molecular sieve, 0.01-0.2 parts of a defoamer and 0.1-0.5 parts of nano-silicon dioxide, and the component B comprises at least isocyanate. The polyol composition comprises at least castor oil, polyether polyol and propylene glycol. The mass ratio of castor oil, polyether polyol and propylene glycol is (20-30): (5-9.7): (0.3-0.4). The polyether polyol comprises polyether polyol 1 and polyether polyol 2. The polyether polyol 1 has a hydroxyl value of 300-400 mgKOH / g and a viscosity of 200-400 mPa·s at 25°C. The polyether polyol 2 has a hydroxyl value of 200-300. mgKOH / g, and a viscosity of 20-200 mPa·s at 25°C; the calcium filler at least includes active calcium, calcium oxide and calcium carbonate; the mass ratio of the active calcium, calcium oxide and calcium carbonate is (5-9.9):1.6:(42.4-63.5).

2. The adhesive for polished aluminum according to claim 1, characterized in that: The mass ratio of the polyether polyol 1 to the polyether polyol 2 is (2-4.5):(3-5.2).

3. The adhesive for polished aluminum of tooling according to claim 2, characterized in that: The particle sizes of the active calcium, calcium oxide and calcium carbonate are 800 meshes to 1250 meshes.

4. The adhesive for tooling polished aluminum according to claim 3, characterized in that: The BET specific surface area of ​​the nano-silicon dioxide is 150-250 m² / g.

5. The adhesive for polished aluminum according to claim 4, characterized in that: The catalyst at least includes a tertiary amine catalyst.

6. The adhesive for polished aluminum of tooling according to claim 5, characterized in that: The dispersant is a divalent acid ester.

7. The adhesive for polished aluminum according to claim 6, characterized in that: The molecular sieve is 4A molecular sieve.

8. The adhesive for polished aluminum of tooling according to claim 7, characterized in that: The defoaming agent at least includes SX08 defoaming agent.

9. The adhesive for polished aluminum of tooling according to claim 8, characterized in that: The mass ratio of component A to component B is 100:(20-30).

10. A method for preparing a binder for polished aluminum according to any one of claims 1 to 9, characterized in that: The method comprises at least the following steps: mixing the polyol composition and nano-silicon dioxide by weight, adding calcium filler and molecular sieve for high-speed dispersion, adding dispersant, catalyst and defoamer for dispersion, cooling to below 50° C. and discharging the material to obtain component A; when in use, mixing component A and component B to obtain the component A.

Citation Information

Patent Citations

  • Polyurethane adhesives and their preparation methods, aluminum honeycomb panels

    CN111454686B

  • Formaldehyde-free plant adhesive and preparation method thereof

    CN115975583A

  • Portfolio polyether, polyurethane adhesive, raw material composition as well as preparation methods of portfolio polyether and polyurethane adhesive and application of polyurethane adhesive

    CN106349450A

  • An adhesive and its preparation and application

    CN112391142A

Cited By

  • Winter jelly-resistant gel for bonding aluminum cellular board and preparation method thereof

    CN120365883A

  • Adhesive as well as preparation method and application thereof

    CN120988635A

  • An adhesive and its preparation method and application

    CN120988635B